Pendekatan Filsafat Pendidikan dan Teori Belajar Humanistik dalam Meningkatkan Kualitas Pendidikan Holistik di Era Digital - Rusdiana Yusuf; I Wayan Suastra; Ananda Wikrama Tungga Atmaja; I Nyoman Tika (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The digital era has brought significant changes to the field of education, creating both new opportunities and challenges. Educational philosophy and humanistic learning theories offer strategic solutions to enhance the quality of holistic education amidst these transformations. This study aims to explore the relationship between educational philosophy, humanistic learning theories, and the application of technology in holistic education. Utilizing a literature review method, this research analyzes various relevant sources to identify key principles and their implications within the context of the digital era. The findings indicate that educational philosophy provides the foundational values needed to maintain a balance between technological innovation and comprehensive human development. Humanistic learning theories, as conceptualized by Carl Rogers and Abraham Maslow, emphasize the importance of meaningful learning and personalization to support the self-actualization of learners. In holistic education, the integration of technology with a humanistic approach can create learning environments that not only facilitate academic achievement but also foster emotional, social, and spiritual development.